A new species of Notacanthurus Tshernova, 1974 (Ephemeroptera: Heptageniidae) from India - Vasanth, M.; Selvakumar, C.; Subramanian, K. A.; Sivaramakrishnan, K. G.; Sinha, Bikramjit (Zootaxa, 2020)
A new species of Notacanthurus Tshernova, 1974 is described based on larvae from India. Notacanthurus pange Vasanth, Selvakumar & Subramanian sp. nov. can be distinguished from all known species of Notacanthurus by the following combination of characters: (i) gill lamellae 5–6 with accessory lobe; (ii) dorsal surface of femora with scattered spatulate setae (iii) male genitalia having penis lobes fused, ‘V’ shaped apically blunt with median pair of spine-like titillators subapically and mesally; (iv) labrum with anterior portion straight and laterally curved; and (v) lingua of hypopharynx apically broad and convex. The distribution map of the new species is also provided.